1985
DOI: 10.1093/nar/13.17.6237
|View full text |Cite
|
Sign up to set email alerts
|

The ribosomal RNA promoter ofAcanthamoeba castellaniidetermined by transcription in a cellfree system

Abstract: The DNA sequences required for faithful initiation of ribosomal RNA transcription were determined. BAL-31 digestion was used to modify the rDNA template by introducing deletions from its 3'- and 5'-ends. The resulting mutant DNAs were tested for template activity individually or in competition with wild type utilizing an in vitro transcription system from Acanthamoeba castellanii. The results identify the sequence extending from -31 to +8 to be absolutely required for transcription. In addition; when the regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 20 publications
3
45
1
Order By: Relevance
“…The minimal promoter detected in these assays is much smaller than in our previous study (15). Remarkably, both Ϫ12 and Ϫ6 are outside the region footprinted by the fundamental transcription initiation factor, TIF-IB, from A. castellanii (21,22).…”
Section: Resultscontrasting
confidence: 52%
See 2 more Smart Citations
“…The minimal promoter detected in these assays is much smaller than in our previous study (15). Remarkably, both Ϫ12 and Ϫ6 are outside the region footprinted by the fundamental transcription initiation factor, TIF-IB, from A. castellanii (21,22).…”
Section: Resultscontrasting
confidence: 52%
“…Previous studies (15,19) identified the region from Ϫ31 to ϩ8 as the minimal sequence necessary to obtain specific transcription initiation. Deletion beyond Ϫ31 resulted in a loss of transcription runoff RNA detectable by autoradiography.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initiation and 3'-O-methyl CTP-limited translocation by RNA polymerase I results in separation of the polymerase-TIF footprints, leaving the TIF footprint unaltered. In contrast, initiation and translocation result in a significant change in the conformation of the polymerase-DNA complex, culminating in an unwound DNA region of at least 10 base pairs.Transcription of the Acanthamoeba castellanii rRNA gene in vitro requires a single transcription initiation factor (TIF) and RNA polymerase I (1,14,17). The properties of this system broadly resemble those of other eucaryotic genes (3,8,24) in that TIF functions by forming a stable complex with the promoter and directs RNA polymerase I to accurately initiate transcription (1,14).…”
mentioning
confidence: 99%
“…This second region is required for TIF binding and can be divided into two portions. One, roughly between -32 and -47, affects the stability of TIF-DNA interactions, and the other, between -31 and -20, is absolutely required for transcription (14,17 (20,23).In previous reports, various aspects of the initiation complex were described (1, 2, 14, 15, 16). In the work described in this report, we combined several approaches to study more dynamic aspects of preinitiation, initiation, and elongating complexes.…”
mentioning
confidence: 99%